PERCEPTION OF LEADERSHIP AMONG HEALTH MANAGERS WORKING IN TERTIARY LEVEL HOSPITALS - Shahzad, Saadia; Zareen, Humaira (Journal of Ayub Medical College Abbottabad, 2012)
Background: Rapid growth of medical knowledge has created major changes in technology which in turn has created greater demand of the client for better health services, and health sector is constantly under pressure of great internal and external demands. Quality of services, largely depend on to what extent managers are well versed with the concept of evidence based management, team and group approach in achieving organizational objectives. Making an effective health system, addressing the double burden of diseases coupled with resource crunch in developing countries is a big challenge for policy makers and health managers. Comprehensive concepts and application knowledge of leadership is very important for health managers in the present day in order to get best output that satisfies all the stake holders. Present anthropological study was done to assess the perception and knowledge of leadership among the health managers working in tertiary level hospitals. Methods: This qualitative study was conducted in two public sector tertiary level hospitals of Lahore chosen randomly out of a total of seven such hospitals in the same city. Convenient sampling technique was used. Observation and in- depth interviews were conducted for data collection. Open ended questionnaire on the lines of MLQ was used. One main domain of leadership was developed and categorisation of the themes was done in the two evolved categories of transformational and transactional leadership. Results: In the domain of leadership 10 of the health managers showed positive themes for transactional leadership, 6 showed positive themes for transformational leadership, and still 1 health manager showed overall negative response for the concept of leadership; he was totally in favour of dictatorship. Conclusion: Health managers with degrees in management/administration had better concept about the key idea of leadership and its variables. Female health managers were more inclined towards transformational leadership behaviour. Keywords: Transformational leadership, transactional leadership, health managers